Suture-Related Keratitis Caused by Corynebacterium macginleyi - Suzuki, Takashi (American Society for Microbiology (ASM), 2007)
We report two cases of suture-related keratitis following penetrating keratoplasty. In both cases, Corynebacterium macginleyi was isolated from corneal specimens. Scanning electron microscopy revealed that corynebacteria could aggregate and form a biofilm. The MICs of sulbenicillin and fluoroquinolones were high for both isolates. Our findings show that C. macginleyi can cause keratitis with biofilm formation.